2022
DOI: 10.1155/2022/3819564
|View full text |Cite
|
Sign up to set email alerts
|

More Liver Metastases Detected Intraoperatively Indicates Worse Prognosis for Colorectal Liver Metastases Patients after Resection Combined with Microwave Ablation

Abstract: Background. Whether more tumor numbers detected in surgery compared to preoperative image affecting survival of colorectal liver metastases (CRLM) patients after hepatectomy combined with microwave ablation (MWA) remains unclear. Methods. From 2013 to 2018, 85 CRLM patients who underwent hepatectomy combined with MWA were retrospectively assessed. Compared to the tumor numbers in preoperative image, patients with equal intraoperative tumor numbers were defined as the equal number group ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The results of Sawada Y et al (39) also suggest that high CA19-9 levels may reflect unfavorable tumor biology, especially in patients with advanced CRLM. Jiang LM et al (40) followed up 85 patients who underwent liver resection combined with microwave ablation for CRLM and found that high CA19-9 levels were a poor prognostic factor for OS. Previously, there was a general focus on CEA and neglect of CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Sawada Y et al (39) also suggest that high CA19-9 levels may reflect unfavorable tumor biology, especially in patients with advanced CRLM. Jiang LM et al (40) followed up 85 patients who underwent liver resection combined with microwave ablation for CRLM and found that high CA19-9 levels were a poor prognostic factor for OS. Previously, there was a general focus on CEA and neglect of CA19-9.…”
Section: Discussionmentioning
confidence: 99%